2017
DOI: 10.1002/tox.22421
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of miR-21 expression in human melanoma via UV-ray-induced melanin pigmentation

Abstract: Excessive environmental ultraviolet (UV) radiation produces genetic mutations that can lead to skin cancer. This study was designed to assess the potential inhibitory activity of microRNA-21 (miR-21) on the UV irradiation-stimulated melanogenesis signal pathway in melanoma cells. The molecular mechanism of miR-21-induced inhibitory activity on UV-ray-stimulated melanogenesis-regulating proteins was examined in A375.S2 human melanoma and B16F10 mouse melanoma cells. UV irradiation for 30 min induced melanogenes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 20 publications
0
19
0
1
Order By: Relevance
“…Previous studies have revealed that some non‐coding RNAs, such as microRNAs, in melanocytes can alter and affect the synthesis of melanin or the development of melanoma under UV stimulation . However, the roles of lncRNAs in modulating melanocyte proliferation and melanogenesis are still unclear.…”
Section: The Indispensable Roles Of Lncrnas In Cutaneous Biologymentioning
confidence: 99%
“…Previous studies have revealed that some non‐coding RNAs, such as microRNAs, in melanocytes can alter and affect the synthesis of melanin or the development of melanoma under UV stimulation . However, the roles of lncRNAs in modulating melanocyte proliferation and melanogenesis are still unclear.…”
Section: The Indispensable Roles Of Lncrnas In Cutaneous Biologymentioning
confidence: 99%
“…Experiments to investigate whether melanin transferred to keratinocytes were affected by the presence of purified EVs showed no altered reaction in cocultures of melanocytes and keratinocytes. Interestingly, Lin et al found that miR21 had an inhibitory effect on UV‐stimulated melanogenesis‐regulating proteins in melanoma cells (Lin, Chen, Lu, Cheng, & Wu, ). In the skin, there is a continuous crosstalk between keratinocytes and melanocytes and we also explored whether purified EVs generated from UVA‐irradiated keratinocytes would affect the ability of melanocytes to produce EVs upon UVA exposure.…”
Section: Discussionmentioning
confidence: 99%
“…For Western blotting, previously reported procedures were followed 1,15,16 . Basically, protein samples were resolved on polyacrylamide gel electrophoresis (SDS‐PAGE) and thereafter, immunoblotted onto a PVDF membrane.…”
Section: Methodsmentioning
confidence: 99%